Analysis of Effect Work Satisfaction on Turnover Intentions With Organizational Commitments as A Mediation Variable - Nugroho, Dermawan; ., Haryadi; Mukti, M. Arifin; Anggraeni, Ade Irma (Jurnal Akuntansi, Manajemen dan Ekonomi, 2020)
This study aims to analyze the effect of job satisfaction on turnover intentions mediated by organizational commitment in employees of the Java Heritage Hotel Purwokerto. The population in this study are all employees who work at the Java Heritage Hotel Purwokerto. The sampling technique in this study uses a cluster proportional random sampling method. The sample used was 94 samples and the data obtained were analyzed using the causal step method in mediation regression analysis. The results of this study indicate that job satisfaction directly has a significant negative effect on turnover intentions, job satisfaction has a significant positive effect on affective commitment, job satisfaction has a significant positive effect on continuance commitment, job satisfaction has a significant positive effect on normative commitment. All three commitments have a significant negative effect on turnover intentions. Continuance commitments and normative commitments each partially mediate the effect of job satisfaction on turnover intentions, while affective commitments cannot mediate the effect of job satisfaction on turnover intentions because most employees of the Java Heritage Hotel are still low on the length of work.